Hematoma Mimicking Liver Mass in a Dog Developed by Spontaneously Ruptured Adrenocortical Adenoma - Kim, Yujin; Kim, Seungwook; Yu, Seung-yeon; Chang, Dongwoo; Lee, Sungin (Acta Scientiae Veterinariae, 2024)
Background: Adrenal tumors can be divided into functional and nonfunctional tumors. Some adrenal tumors can induce hyperadrenocorticism, e.g., adrenocortical carcinoma or adenoma and pheochromocytoma. Patients with nonfunctional adrenal tumors may present without any symptoms associated with excessive catecholamines or corticosteroids, including polyuria, polydipsia, panting, potbelly, polydipsia, and hypertension. Adrenal tumors that present no clinical signs and are detected incidentally on diagnostic imaging are called incidentalomas. Incidentalomas sometimes rupture spontaneously without trauma, resulting in a hemoabdomen and hematoma. Herein, a ruptured benign adrenal gland tumor created a large hematoma that mimicked a liver mass on computed tomography (CT) scans. These findings can support surgeons managing a ruptured adrenal gland tumor or 2 or more masses suspected on CT scans. Case: A 13-year-old neutered male poodle, weighing 6.98 kg, was presented with abdominal distension and lethargy. Physical examination revealed prolonged capillary refill time (CRT), pale mucous membranes, decreased blood pressure, and elevated portable lactate values. In blood analysis, aPTT and PT were mildly prolonged, and the D-dimer value was elevated. Abdominal mass and fluid were defined on ultrasonography, and abdominocentesis was performed. Sanguineous fluid was collected. The patient had no history of any traumatic events to indicate the likelihood of an abdominal mass rupture. Subsequent CT scans revealed 2 masses in the right adrenal gland and the caudate lobe of the liver. High attenuation in the adjacent parts between the masses suggested mass adhesion or invasion of the adrenal mass into the liver. After blood transfusion, hemodynamic values did not improve; therefore, an exploratory laparotomy was performed. During surgery, the suspected liver mass was found to be a large hematoma distributed throughout the abdomen. The liver exhibited no gross pathological findings. After the removal of the suspected hematoma, right adrenalectomy was performed, and part of the hematoma was separated without intentional modification. On histopathological examination, the right adrenal tumor was defined as an adrenocortical adenoma and the hematoma was defined as an adrenocortical adenoma with marked hematoma formation. Adrenocorticotropic hormone (ACTH) levels were within the normal range, ruling out hypoadrenocorticism. After 9 months of the surgery, the patient showed no clinical signs of any adrenal gland dysfunction or hemodynamic problems. Discussion: An adrenocortical adenoma rupture is rare. This is the 1st veterinary case of a hematoma-mimicking liver mass originating from a ruptured benign adrenal tumor. The mass, thought to be a liver mass, showed a CT scan pattern similar to that of the primary liver mass reported in a previous canine study. This hematoma showed the pattern of a ruptured adrenal gland that could be indistinguishable from the adrenal tumor in a human study, which could suggest it as being the sole tumor, not a hematoma. Moreover, its characteristic histopathological findings indicated that it was a hematoma mixed with adrenocortical neoplastic tissue. This condition might generate CT patterns similar to those of other masses. The location of hematoma formation defined on CT scans may suggest to surgeons that the hematoma is a liver mass. Surgeons who encounter this complication should consider the likelihood of hematoma formation. Keywords: hematoma, computed tomography, adrenal gland tumor, incidentaloma, adrenalectomy, spontaneous rupture.